1988
DOI: 10.1113/jphysiol.1988.sp016936
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to cold on metabolic characteristics in gastrocnemius muscle of frog (Rana pipiens).

Abstract: SUMMARY1. Responses of enzymic characteristics of gastrocnemius muscle were studied when frogs (Rana pipiens) were exposed to cold environment (4 0C).2. The content of adenosine triphosphate (ATP) decreased significantly after cold exposure. This decrease was greater in starved than in fed frogs.3. Although the glycogen content did not change, lactate levels were lower in coldexposed than room-temperature (control) frogs. No change was observed in glycogen and lactate between fed and unfed frogs kept at 4 0C f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Low temperatures were found to affect vertebrate muscles similarly. in frog gastrocnemius muscle (Ohira & Ohira 1988), the content of ATP decreased after cold exposure, this decrease being greater in starved individuals.…”
Section: Seasonal Metabolite Changes In Resting Prawnsmentioning
confidence: 99%
“…Low temperatures were found to affect vertebrate muscles similarly. in frog gastrocnemius muscle (Ohira & Ohira 1988), the content of ATP decreased after cold exposure, this decrease being greater in starved individuals.…”
Section: Seasonal Metabolite Changes In Resting Prawnsmentioning
confidence: 99%
“…It has been reported that an adaptation of the metabolic and contractile properties of skeletal muscles is induced in response to cold exposure [1][2][3]. An improved fatigue resistance of fast-twitch extensor digitorum longus (EDL) muscle, but not of slowtwitch soleus muscle, in response to train stimulation at 10 Hz (100 ms train duration, 60 trains/min) was induced following 20-week intermittent cold-water immersion in rats [1].…”
mentioning
confidence: 99%
“…OHIRA, M. KANZAKI, and C.-S. CHEN clusions were induced in rat soleus muscle in response to acute ischemia caused by ligation and sectioning of the abdominal aorta. Although the intramitochondrial inclusions were not reported, similar enlargement of mitochondria (YAHATA and KUROSHIMA,1977) and increased mitochondrial enzyme activity (OHIRA and OHIRA, 1988) were also induced by cold acclimation. The common phenomenon between cold-acclimated, ischemic, and f3-GPA-treated muscles are lowered levels of PC and ATP.…”
Section: And Discussionmentioning
confidence: 99%
“…Cold acclimation of rats also increased the activity of succinate dehydrogenase in soleus muscle fibers (MATOBA and MURAKAMI, 1981), although the mechanism of morphological and metabolic changes in mitochondria is still unclear. However, our previous study showed that the activity of gastrocnemius oxidative enzymes were elevated when the contents of adenosine triphosphate (ATP) were decreased following the chronic exposure to cold (4°C) In frogs (OHIRA and OHIRA, 1988). …”
mentioning
confidence: 99%